Globalisasi Budaya Bagi Mahasiswa Indigenous Papua Di Arus Perkembangan Kota - Kabanga, Lewi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The nature of globalization is breaking through the geographical boundaries of area and changing the forms that have been established before. Cultural globalization seems to create new culture. The purpose of this research is to give description about the existence of Globalization in language and inter-racial marriage in Jayapura. This research used descriptive qualitative method.  The object of this research was the indigenous students of Papua in Jayapura. Places to obtain the data were in student’s dorms such as Biak, Fak-fak, Wamena and Meraukes’s dorms. Focus Group Discussion (FGD) was the single manner in collecting data. This technique applied semi-structured way in which the researcher developed and dig elaborately the questions to find the core answers. Recording was the way documented FGD. Recorded data was transcribed and then reduced by classifying and indexing features of globalization in language and inter-racial marriage. The findings were analyzed and described based on contextual phenomenon. The result of this research revealed that (1) language phenomenon was in cost and benefit of practical used, they tended to “code mix” in order to broad the scope area of their communication, moreover with this term their social relation could be run effectively. (2) inter-racial marriage responds were caused by both internal and external factors that indicated the attitude to face the similar case